KENDALA DAN RINTANGAN MEMBANGUN PEMERINTAHAN YANG BERSIH DAN BERWIBAWA - Edwin Yuliska (Ensiklopedia Education Review, 2023)
The realization of a person's socio-economic life is inseparable from the human effort itself with all available resources and efforts and is influenced by several driving factors, including the urge to defend oneself in life from various influences. The creation of expanded job opportunities for the wider community is a reflection of Article 33 of the 1945 Constitution, where the prosperity of the people is prioritized, not the prosperity of individuals. Utilizing natural resources for the greatest prosperity of the people by taking into account the preservation of functions and balance of the environment, sustainable development, economic and cultural interests of the surrounding community and environmental spatial planning that supports each other. Therefore, sensitivity and serious concern are required for the phenomena of life which are increasingly worrying about the social turmoil of the nation and state, therefore all parties should also spark a movement for change in opening up broad employment opportunities, one of which is to provide space for facilities and infrastructure. to develop creativity and entrepreneurial potential.Keywords: Constraints, Barriers, Government, Clean, Authoritative.